Ulama Nusantara’s Legacy: Study of Hadith in the Book of Nuṣūṣ al-Akhyār fī al-Ṣawm wa al-Ifṭār in Hasan Hanafi's Hermeneutic Perspective - Anam, Wahidul; Sulaeman, Mubaidi; Ali, Zezen Zainul (Universitas Islam Negeri Mataram, 2024)
This research examines the Prophetic traditions contained in the book